Anterior pericranial flap for frontal sinus duct obliteration: Is it a valuable resource? - De Melo, Willian Morais [UNESP]; Coléte, Juliana Zorzi [UNESP]; Mariano, Ronaldo Célio; Shinohara, Elio Hitoshi [UNESP]; Souza, Francisley Ávila [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP] (Wolters Kluwer, 2013)
Inappropriate treatments of frontal sinus fractures may lead to serious complications, such as mucopyocele, meningitis, and brain abscess. Assessment of nasofrontal duct injury is crucial, and nasofrontal duct injury requires sinus obliteration, which is often accomplished by autogenous grafts such as fat, muscle, or bone. These avascular grafts have an increased risk of resorption and infection and donor site morbidity. For these reasons, pericranial flap, which is vascular, should be used for frontal sinus obliteration. The pericranial flap presented with less morbidity procedure and has decreased infection rates, which justifies its use in frontal sinus obliteration. This study aimed to report a case of a comminuted frontal sinus fracture with a brief literature review, regarding the use of pericranial flap. The authors report a case of a 23-year-old male subject with a severely comminuted fracture of the anterior and posterior walls of the frontal sinus. The patient was successfully treated by cranialization with frontal sinus duct obliteration, using anterior pericranial flap. The patient was followed up for 16 months with no postoperative complication, such as infection. Pericranial flap is a good resource for frontal sinus duct obliteration because it is a durable and well-vascularized flap, which determines low rates of postoperative complications. Copyright © 2013 by Mutaz B. Habal, MD.
Keywords: Facial fracture; Frontal sinus; Galeal frontalis myofascial flap; Infection; Sinus obliteration; Titanium plate